The Existence and Form of Tafsir al-Munir by Wahbah al-Zuhaili - Damanhuri, Damanhuri (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Wahbah al-Zuhaili is a well-known scholar who was born in Damascus. He is known for his book Tafsir al-Munir, which explains how to interpret the Quran in a way that is easy to understand and digest. Using a qualitative approach, the goal of this study is to look at different parts of Tafsir al-Munir that have to do with its existence and form, such as the style of interpretation, the methods of interpretation, and the unique parts of the work. The conclusion drawn from this study is that Tafsir al-Munir, written by Sheikh Wahbah al-Zuhaili, is a highly specific and systematic work with complete and perfect explanations, clear and vivid language, and a prominent presence in the field of Quranic interpretation in modern times. In terms of methodology and analysis, it appears that the style of interpretation of Tafsir al-Munir is characterized by literary and socio-cultural elements, as well as nuances of Islamic jurisprudence (fiqh) in its interpretation.